Pengabdian Masyarakat Kegiatan Bersih-Bersih dan Penyuluhan Usaha Kampung di Cadasngampar oleh Mahasiswa IIUM Bersama IAI Tazkia - Ismail, Nurizal; Nuriyah, Aminah; Surur, Miftakhus; Rahman, Faried Kurnia; Ibrahim, Muhammad Yusuf (Tazkia Islamic University College, 2024)
The community service of IIUM students in collaboration with IAI Tazkia encompasses two activities focusing on village cleanup and education in Kampung Cadasngampar. The first activity involves cleaning the village with the intention of preserving and tidying up the environment within a village or settlement. This activity goes beyond physical cleanliness, aiming to create environmental awareness and concern for the cleanliness of the surroundings. Additionally, students are also engaged in educational activities with school dropouts. The purpose of this initiative is to provide informal learning opportunities for children who have discontinued formal schooling or lack access to formal education. Through this interaction, they strive to provide education and basic skills to children, enabling them to develop their potential even without following the formal education path. This community service reflects the commitment of IIUM students and IAI Tazkia to make a positive impact on the local community, addressing both environmental cleanliness and informal education for those in need.